Konsep Balance Scorecard Dalam Strategi Bisnis dan Pendidikan serta Deskripsi Implementasinya pada SMK Negeri 6 Garut Melalui Pendekatan Manejemen Berbasis Sekolah (MBS) - Arman Paramansyah; Acep Dani Ramdani; Ipan Sopandi; Eddy Suharyanto; Ryan Yustian; Iim Wasliman; Eva Dianawati (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The concept of the Balanced Scorecard has been widely implemented in various business fields, both goods and services, so that by studying this concept the reader can understand the meaning, purpose, benefits, factors that are the key to the successful implementation of the Balanced Scorecard. The purpose of this study is to implement the Balanced Scorecard at SMK NEGERI 6 Garut. This research method uses a qualitative approach with library research methods, both in books, articles, journals, or online media which discusses the analysis of educational management standards accompanied by field studies using interview techniques and descriptive surveys using simple questionnaires. The Balanced Scorecard in business functions to provide guidance in determining the objectives and measures of the Scorecard, obtaining commitment from project participants and clarifying the framework for implementation, and the management process that must be carried out after the initial scorecad preparation. In business, it is a management tool used to boost an organization's ability to multiply performance. Keywords: Balanced Scorecard, Implementation, Business & Education Strategy, School Based Management’